Environmental literacy of pupils and its investigation in the Czech Republic - Silvie Svobodová (Sociální Pedagogika, 2020)
Environmental literacy is a concept consisting of knowledge, attitudes, sensitivity and behaviour. In this text we present a pilot study of a research tool focused on measuring the environmental literacy of ISCED 2 pupils. Through the study we measured the relationship between environmental literacy and selected variables (gender, grade and leisure activities). The target group consisted of pupils in the 6th to 9th grades of lower secondary schools, and the total number of respondents was 467. The inner consistency (Cronbach´s α) of all tool scales (knowledge, attitudes, sensitivity, behaviour) reached acceptable values in the range of .71–.79. Spearman’s correlation showed a statistically significant relationship mainly among the scales of attitudes, sensitivity and behaviour. Significant correlation coefficient values ranged from < .44 to .65 >. Significant differences appeared between boys and girls in regard to attitudes, sensitivity and behaviour scales, where girls reached higher scores. Girls showed more pro-environmental attitudes, sensitivity and behaviour than boys. It was also found that the pupils' environmental knowledge increases with age. However, this does not apply to the scales of attitudes, sensitivity and behaviour. There was a high correlation between environmental literacy (excluding knowledge) and the leisure activities of pupils (outdoor activities, ICT, hobbies and sport). Leisure activities in combination with age can be considered essential determinants of environmental literacy, e.g. they predict 33% of the variability in the sensitivity scale.